2012
DOI: 10.1590/s0102-311x2012001400009
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with asymptomatic infection in family members and neighbors of patients with visceral leishmaniasis

Abstract: This study analyzed factors associated with asymptomatic Leishmania chagasi infection in family members and neighbors of patients with visceral leishmaniasis (VL). A cross-sectional study was conducted with 361 individuals in the counties comprising Ilha de São Luís (São Luís Island) in Maranhão State, Brazil. The Montenegro skin test (MST) and serology by enzyme-linked immunosorbent assay (ELISA) were performed to detect infection. Odds ratios (OR) and prevalence ratios (PR) and their 95% confidence intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…As mentioned by other authors 29,30 , it was found that most cases of HAVL were concentrated in the urban perimeter of the municipalities and, despite a higher prevalence of the disease in males in others regions of Sao Paulo State 23,31 , no significant difference between genders was observed in the studied microregion, corroborating the results obtained by Vieira et al 28 in Birigui, Sao Paulo State, and Moura et al 32 in the island of Sao Luis, Maranhao State. The HAVL equal incidence between genders can be attributed to the predominance of urban cases, an environment in which there is no tendency for men to be more exposed to a harsh environment than women 28 , unlike the situation in rural areas 33 .…”
Section: Discussionsupporting
confidence: 87%
“…As mentioned by other authors 29,30 , it was found that most cases of HAVL were concentrated in the urban perimeter of the municipalities and, despite a higher prevalence of the disease in males in others regions of Sao Paulo State 23,31 , no significant difference between genders was observed in the studied microregion, corroborating the results obtained by Vieira et al 28 in Birigui, Sao Paulo State, and Moura et al 32 in the island of Sao Luis, Maranhao State. The HAVL equal incidence between genders can be attributed to the predominance of urban cases, an environment in which there is no tendency for men to be more exposed to a harsh environment than women 28 , unlike the situation in rural areas 33 .…”
Section: Discussionsupporting
confidence: 87%
“…32 In addition, there was a significant association between asymptomatic infection and proximity of human residences to animal shelters (p<0.01) indicating that animal shelters and loose soil surrounding them are suitable breeding sites for Phlebotomus argentipes. 33 Since the flight range of the phlebotomine sand fly is estimated to be up to 200 meters, 20 the disease prevalence is likely to be enhanced when residing within the vector flight range from their breeding sites. The restricted flight range could also explain why there was a greater tendency of detecting asymptomatic sero-positive individuals whose houses were close to water bodies (p=0.05).…”
Section: Discussionmentioning
confidence: 99%
“…We chose family members and adjacent neighbours as contacts of these patients with VL because sand flies have a short flight range of up to 200 meters. 20 Using a non-probability sampling technique, we selected a total of 257 contacts, of which 80.9% (208/257) were family members and 19.1% (49/257) were adjacent neighbours. Inclusion criteria were: age between 2 and 75 years old; either sex; clinically healthy with no previous history of VL or PKDL; family member residing in the same household as patients with VL or adjacent neighbours without VL cases in the household; and voluntary consent to participate in the study.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…3,4 Family members and neighbors of patients with a history of classic VL are more susceptible to acquiring the disease due to similar exposures. 5 In our report, the patient was young and she had no underlying diseases; her risk factors consisted of living in a rural area, and a daughter with a recent diagnosis of Leishmaniasis. She showed the typical clinical features of the disease, with fever, hepatosplenomegaly and pancytopenia.…”
Section: Discussionmentioning
confidence: 66%
“…The complete blood count demonstrated a white blood cell count of 2850 cells/mm3, haemoglobin 11.8 g/dL, platelets 84000-111000 cells/mm3; erythrocyte sedimentation rate 48 mm/h, C-reactive protein 9.12 mg/dL and a very slight increase of gamma globulins (19.3% at the serum protein electrophoresis, range value 10, [5][6][7][8][9][10][11][12][13][14][15][16][17][18]8). Physical examination demonstrated hepatosplenomegaly, confirmed by ultrasound (spleen size approximately 20 cm).…”
Section: Case Presentationmentioning
confidence: 99%